Special populations: The female player and the youth player - Rosenbloom, C. A.; Loucks, A. B.; Ekblom, B. (Journal of Sports Sciences, 2006)
Females and youth are frequently described as "special" populations in football literature, but together these two populations outnumber male players. What makes females "special" is that they tend to eat less when training and competing than their male counterparts, leading to lower intakes of energy, carbohydrate, and some nutrients. Youth football players are special in regard to energy and nutrient requirements to promote growth and development, as well as to fuel sport. There is limited research on the dietary habits of these two populations, but the available literature suggests that many female and youth players need to increase carbohydrate intake, increase fluid intake, and develop dietary habits to sustain the demands of training and competition.